Prevalence of Taurodontism in the United Arab Emirates: A Retrospective Study with a Global Comparison - Narasimhan, Sangeetha; Shetty, Shishir R.; Kamath, Vinayak; Al-Daghestani, Hiba S.; Gopinath, Vellore K. (European Journal of Dentistry, 2025)
Taurodontism is a developmental dental anomaly that can significantly impact various dental treatment procedures. This study retrospectively investigated the prevalence of taurodontism in the United Arab Emirates (UAE) and compared it with global prevalence rates.A total of 1,355 panoramic radiographs were retrospectively examined to identify cases of taurodontism. An extensive review of the literature was performed across three databases to identify studies reporting the global prevalence of taurodontism.The global prevalence data were compared with findings from the UAE using Fisher's exact test or chi-square test.The prevalence of taurodontism in Sharjah (UAE) was 0.66%. It was observed three times more frequently in the mandible (73.3%) than in the maxilla (26.7%). The mandibular second molar (46.7%) was the most affected tooth. Hypotaurodontism (66.7%) was the most prevalent type identified in the study. The pooled prevalence of taurodontism in the UAE was 1.4%, which closely aligned with the average prevalence observed in Middle Eastern countries. Based on the retrieved literature, North America recorded the highest prevalence at 31.3%, whereas the Middle East had the lowest prevalence at 1.9%.Taurodontism is less prevalent in the UAE compared with other regions worldwide. Globally, the occurrence of taurodontism varies significantly, with the highest prevalence rates reported in Canada, China, and Brazil. These differences may be influenced by genetic and environmental factors, variations in diagnostic methodologies, sample sizes, and inconsistencies in the inclusion and exclusion criteria applied across studies.
Keywords: taurodontism; taurodont; dental anomalies; prevalence; enlarged pulp chamber; bull-like teeth